EFL Undergraduate Students’ Professional Identity Construction: A Sociocultural Perspective - Cicilia Siwi Triutami; Concilianus Laos Mbato (Universitas Bengkulu, 2021)
Social relationship within a sociocultural context is considered to be one of the influencing factors involved in the process of teacher identity. The process is both complex and dynamic in which it demands individuals’ continual struggle and change due to the involvement of external and internal factors. This study investigated the process of professional identity construction of two EFL undergraduate students through their engagement in the educational environment and the teaching practicum context. The participants involved in this study were at the eighth academic semester of the Teacher-Education Study Program at University of Papua (UNIPA), Manokwari, Papua Barat and they had accomplished their teaching practicum in high schools in Manokwari. The student-teachers built their social interactions at with their peers and teacher-educators within their educational environment at the university and with their mentor-teachers, students and supervisors in their teaching practicum. A qualitative research was employed through semi-structured interview. The findings revealed that the process of students’ professional identity construction is both dynamic and unstable and shaped by the three intertwined factors in the identity construction process namely: self-perception, educational environment, and teaching practicum. The students’ self-perception changed through the process as an impact of their interactions with educational environment and teaching practicum. The significance of the contentment and impediments as the dimensions of these experiences shaped the students’ professional identities.